Consonants that Disrupt Acoustic Harmony Rule in Old Anatolian Turkish : ESKİ ANADOLU TÜRKÇESİNDE ÜNLÜ UYUMUNU BOZAN ÜNSÜZ HARFLERİ (Journal of the College of Languages (JCL), 2023)
There are many changes in words and suffixes in the ancient Anatolian Turkish language. One of these changes is the obstruction of consonants phonemes in Old Anatolian Turkish. This obstruction was the reason for the approximation in the ancient Anatolian Turkish phonemes. The most important aim of this study is to show this approximation.The research plan, before engaging the study, clarifies the general reasons and the opinions of Turkish linguists about the consonants that obstruct phonemes in the ancient Anatolian Turkish words and their suffixes, and we illustrate with examples the effect of the consonants that obstruct phonemes in ancient Anatolian Turkish words with an attempt to evaluate it. Then divide the examples that we used into two parts, first is examples about the Turkish linguists’ books, while the second is about some texts of the ancient Anatolian Turkish language, such as Yusuf Zulaikha and Soheil Nobehar.The aim of the study is to explain the reasons and the changes in the form of ancient Anatolian Turkish words and their suffixes based on examples from the most famous books of Turkish linguists to present them to the researcher and learner of the ancient Anatolian Turkish language.ÖzetEski Anadolu Türkçesinde kelime ve eklerde çeşitli değişiklikler vardır. Eski Anadolu Türkçesinin seslerinde Dudak Uyumu Bozulması, bu değişiklerinden biridir. çünkü Eski Anadolu Türkçesinin seslerinde yuvarlaklaşma sebebi idi. Bu çalışma en önemli amacı bu değişmiş yuvarlaklanmışını göstermektir .Çalışma planı, çalışma konusuna girmeden önce Türk dilcilerin Eski Anadolu Türkçesinin kelimleri ve eklerinin seslerinde Dudak Uyumu Bozulması hakkındaki genel sebebleri ve göüşlerini izah ederek, Eski Anadolu Türkçesinin kelimlerinde seslerinde Dudak Uyumu Bozulması örnekle izah ederk, Eski Anadolu Türkçesinin eklerinin seslerinde Dudak Uyumu Bozulması örnekle izah ederk, düzlenmeye çalıştık. Kullandıklarımız örnekler ikiye ayrılır biri Türk dilciler kitaplarının örnekleri, bazı Eski Anadolu Türkçesinin metinlerinden örnekleriydi ‘‘Yusuf u Zeliha ve Süheyl ü Nev Bahar ’’ gibidir.Çalışma gayesi, Eski Anadolu Türkçesinin hakkında Araştıran ve Öğrenene sunmak için Eski Anadolu Türkçesinin kelimleri ve eklerinin seslerinde Dudak Uyumu Bozulmasının sebepleri ve şekil değişilmesinin örneklerle ve en ünlü Türk .dilcilerini kitapların dayanarak izah etmektedir